Autophagy, physiology and cell pathology - Vaccaro, María Inés (2013)
Autophagy plays an important role in human pathologies, such as miopathies and neurodegenerative diseases. Moreover, metabolic disease processes such as diabetes and pancreatitis, as well as tumor cells and cancer chemotherapy, activate autophagy. Furthermore, a selective type of autophagy of pancreatic zymogen granules has been discovered and characterized as a protective cellular process triggered by acute pancreatitis. In this review we describe the physiological bases and molecular mechanisms in the autophagic process and the possible role of autophagy in human disease. Understanding the events and molecular mechanisms of this complex cellular process will help in the design of new strategies for more effective diagnosis and treatment.